Attitudes towards dementia among Chinese adults aged 50 years and older: a comparative study of immigrants living in Melbourne and nonimmigrants living in Beijing. (3rd January 2023) - Zhao, Mei; Zhang, Haifeng; Lin, Xiaoping; You, Emily; Wang, Huali; Lautenschlager, Nicola T.
ABSTRACT: Objectives: This study investigated attitudes towards dementia among Chinese immigrants aged 50 years and over living in Australia and compares these attitudes with those of individuals living in mainland China. It aimed to better understand what older Chinese adults think about dementia and to inform the development of tailored dementia-related services for this group of people. Design: A qualitative design involving individual interviews was employed in this study. Participants: Forty-six participants were recruited: 21 in Melbourne and 25 in Beijing. All interviewees were born in mainland China, were community-dwelling, and did not have a dementia diagnosis. Measurements: The tripartite model of attitudes was used to guide the semi-structured interview design and report the results. Thematic qualitative analysis was employed. Results: In both groups, most participants held negative feelings, stigmatized views and negative stereotypes of dementia. However, most participants expressed a willingness to help individuals living with dementia. Regarding dementia care, nearly all participants preferred home care but thought formal care would become the mainstream form of care in the future. Fewer Melbourne participants expressed concerns regarding developing dementia, were interested in dementia, or perceived a need for dementia-related educational activities. Melbourne participants also reported more avoidant responses to dementia or individuals living with dementia. Conclusion: This study carefully compares attitudes towards dementia between older Chinese immigrants in Melbourne and older Chinese adults in Beijing. Similarities and differences were observed between these two groups. Dementia-related service providers should consider the sociocultural changes and migration-related barriers experienced by Chinese immigrants.